FAKTOR-FAKTOR YANG MEMENGARUHI PENGUNGKAPAN TATA KELOLA PERUSAHAAN DAN DAMPAKNYA TERHADAP KINERJA PERUSAHAAN - Salman, Putriana; Nurkholis, Nurkholis; Mardiati, Endang (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
Title: [Factors that Affect the Disclosure of Corporate Governance and its Impact on Corporate Performance]This study aims to analyze factors that affect the disclosure of corporate governance and its impact on firm performance. The factors investigated include firm size, listing age, board size, proportion of independent directors and audit committee size. This study used 161 companies listed in Indonesia Stock Exchange by using purposive sampling. The results show that company size, board size, proportion of independent directors, and audit committee size significant affect corporate governance disclosure. Furthermore, this study show that disclosure of corporate governance has significantly positive impact on firm performance as measured by Tobin’s Q. The firm performance as measured by ROA is not affected by the disclosure of corporate governance.